Effect of Ventilation on Occupational Exposure to Airborne Biological Contaminants in an Isolation Room - Jafari, Mohammad Javad (Tanaffos, 2015)
BACKGROUND: Airborne pathogens play an important role in a hospital air quality. Respiratory infections are the most common occupational disease among the health care staff. The aim of this study was to determine the effect of ventilation system parameters and patient bed arrangements on concentration of airborne pathogens in indoor air of an isolation room. MATERIALS AND METHODS: A single-bed room was considered in which a patient diagnosed with tuberculosis had been admitted. Five different ventilation types, each at four different capacities were installed in the room while two different locations for the patient’s bed were assessed. A direct-impact sampling method (blood agar plate) was used in order to determine the intensity of the bio-aerosols in indoor air of the isolation room. RESULTS: The results showed that when the air was supplied through a circular vent located on the northern wall and the vented air was exhausted via a linear vent located on the southern wall, the average concentration of the bio-aerosols in the air, (with 12 air changes per hour) was reduced to 25 colonies per cubic meter (cfu/m(3)) (in the range of 25–88 cfu/m(3) and a 95 percent confidence interval). In accordance with the analysis applied upon the two different locations of the bed, no significant difference was observed (P>0.05). CONCLUSION: Installation of ventilation systems as determined by the study is recommended for tuberculosis isolation rooms.